The grammar of supervision: Utilising the pedagogies of representations, decomposition, and approximations of practice in doctoral supervision within the humanities and social studies - Christiansen, Iben Maj (Högre utbildning, 2025)
Teaching and supervision invite students to study and make sense of the world anew. The practices of study and research enable this work of students. To learn the practice of research, the processes and products of research and the relationships between them must be made visible to novice researchers both conceptually and operationally. To learn doctoral supervision, the processes and products of supervision and the relationships between them must be made visible to novice supervisors. This implies clearly linking supervision processes to the core practices of research that must be “taught” to the novice researchers. In this paper, I touch on two practices of research in the humanities and social sciences that many doctoral students experience as challenging: (i) synthesising literature, and (ii) operationalising theory. For each, I will discuss how the pedagogies of representations, decomposition, and approximations of practice may be utilised in the supervision. Hence, this paper aims to contribute to a strengthening of the discourse of doctoral supervisory pedagogy.